Towards a comprehensive regulation of criminal mediation (Acta Judicial Journal, 2022)
This article anticipates the main challenges that may be faced by a necessary and future comprehensive regulation of development of the criminal mediation procedure. The configuration of the access or eventual referral to the criminal mediation services must be understood from the insufficient regulation provided by article 15 of Law 4/2015, of April 27, of the Statute of the victim of the crime. Same identity of reason with respect to the development of the criminal mediation sessions and the delimitation of the applicable principles. The above, in addition, must be harmonized with the regulatory provisions that may be applicable both in criminal and criminal procedural matters.